PENINJAUAN PENGARUH BEBAN GEMPA TERHADAP STRUKTUR ATAS YANG BERINTERAKSI DENGAN TANAH DENGAN JENIS PONDASI SETEMPAT - sinta Dewi Fajarelia; Pujo Priyono; Arief Alihudien (HEXAGON, 2017)
Indonesia's geological condition has earthquake potential that covers most of its territory. To reduce the risk of disaster, it needs earthquake resistant building construction. Generally in existing calculations, the calculation of earthquake loading that is assigned to the ETABS program or SAP 2000 is the result of manual data input and placed at the center of each floor by assuming the upper and lower structure (foundation) are separate. In fact, the structure and the ground (foundation) become a unity.The study was conducted by analyzing the magnitude of the reaction due to conventional analysis to be equivalent to spring by taking into account the amount of the support settlement.The results of the study showed that the momentary support of the exterior beam interaction analysis (spring) decreased for all floors. While in the field moment the beam of interaction analysis (spring) increased, and at the moment of the pedestal beam interior interaction analysis (spring) increased. Keywords : Consolidation, Impact of earthquake loads on soil, immediate settlement.